Adoption of E-Business and Business Performance of Hotel Sector in Sri Lanka - Samaraweera, D.S.; Jayasiri, N.K. (My University, 2016)
The aim of this study is to identify the factors or antecedents which influence the intensity of adoption of e-business in hotel sector in Sri Lanka and to investigate the relationship between intensity of e-business adoption and business performance. The study was completed within three months. This study develops a conceptual framework to capture antecedents and derive hypothesis. Quantitative method is used as research strategy. Questionnaire was distributed to 50 hotels in order to gather data. Multiple regression model is used as analytical technique. The results depict that organisational learning ability and customer power have significant influence on intensity of adoption of E-Business. The customer orientation and top management emphasis individually do not have significant influence on intensity of adoption of E-Business. However, all the variables jointly influence the intensity of adoption of E-Business. The study further reveals that the intensity of adoption of E- Business has a positive impact on the business performance, thus, improves the performance of hotels in Sri lanka.
Keywords: E-Business; Business Performance; Hotel Sector; Sri Lanka